NMDA receptor-dependent synaptic activation of TRPC channels in olfactory bulb granule cells - Stroh-Vasenev, Olga; Freichel, Marc (The journal of neuroscience, 2012)
Canonical transient receptor potential (TRPC) channels are widely expressed throughout the nervous system including the olfactory bulb where their function is largely unknown. Here, we describe their contribution to central synaptic processing at the reciprocal mitral and tufted cell-granule cell microcircuit, the most abundant synapse of the mammalian olfactory bulb. Suprathreshold activation of the synapse causes sodium action potentials in mouse granule cells and a subsequent long-lasting depolarization (LLD) linked to a global dendritic postsynaptic calcium signal recorded with two-photon laser-scanning microscopy. These signals are not observed after action potentials evoked by current injection in the same cells. The LLD persists in the presence of group I metabotropic glutamate receptor antagonists but is entirely absent from granule cells deficient for the NMDA receptor subunit NR1. Moreover, both depolarization and Ca2+ rise are sensitive to the blockade of NMDA receptors. The LLD and the accompanying Ca2+ rise are also absent in granule cells from mice deficient for both TRPC channel subtypes 1 and 4, whereas the deletion of either TRPC1 or TRPC4 results in only a partial reduction of the LLD. Recordings from mitral cells in the absence of both subunits reveal a reduction of asynchronous neurotransmitter release from the granule cells during recurrent inhibition. We conclude that TRPC1 and TRPC4 can be activated downstream of NMDA receptor activation and contribute to slow synaptic transmission in the olfactory bulb, including the calcium dynamics required for asynchronous release from the granule cell spine.